AKTUALISASI SEMANGAT KEBANGSAAN DALAM MENYIKAPI WABAH COVID 19 DI SMP MUHAMMADIYAH 1 PURWOKERTO - Elly Hasan Sadeli; Eko Priyanto; Banani Ma’mur (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research aims to get actual and factual information about the actualization of the national spirit in responding to the covid 19 outbreak at Muhammadiyah 1 Purwokerto Junior High School. The research process uses a qualitative approach with case study methods. Data collection techniques are carried out through observation, interviews, documentation studies and literature studies. This research was conducted on the learning process of Pancasila Education and Citizenship (PPKn). Subjekresearch is the principal, teacher PPKn and student. The findings in this study show that; 1) Students do not yet have a complete understanding of the concept of national insight, but implicitly in the process of learning PPKn, teachers always build a climate of togetherness and help each other. This condition can actually be understood if the seeds of the national spirit have appeared. The selection of varied learning methods is used by PPKn teachers and IPS teachers, which support the national attitude of students. PPKn and IPS learning carried out contributes considerable in shaping the national spirit of students in school which is characterized by the direction of achievement of learning success that not only looks at cognitive aspects, but also emphasized on affective and psychomotor aspects, especially those that are charged with national values. 2) Strengthening the organization with the foundation of the spirit of nationalism based on state ideology and Muhammadiyah values. Through a strong organizational commitment, the spirit of nationality flows in students. 3) The practice of the student's national spirit is realized through its participation in scouting activities (Hizbul Wathan/ HW scouting), flag ceremony activities, sports competitions, and regional arts events are a form of stimulation in developing national values in students and not spreading hoax news about the covid 19 pandemic.